GAME INTERAKTIF 3 DIMENSI SEBAGAI ALAT BANTU BELAJAR BERHITUNG BAGI ANAK KELAS 1 SD - Katharina Ineke Chandra; Moh. Sofyan S. Thayf; Hamdan Arfandy (KHARISMA Tech, 2018)
The purpose of this research is to design a multimedia application that can help students in learning to count and play. This app can run only on smartphones. Implemented using Unity with C # programming language. The program was tested using black box testing method. In this application, the introduction and operation of numbers just until 20 only. Based on the results of research and testing can be concluded that the author has managed to build a 3 Dimensional Interactive Game as a Counting Learning Tool For Grade 1 Elementary school children.